Exploring students’ entrepreneurial motivation and interest in developing innovative business ideas for future careers - Santra, I Ketut; Kencanawati, Anak Agung Ayu Mirah; Winaya, Ni Nyoman Teristiyani; Masih, Ni Ketut; Jaya, I Made Sura Ambara (YAYASAN MITRA PERSADA NUSANTARA, 2025)
This study investigates the factors that influence entrepreneurial motivation and intention among Business Administration students at Politeknik Negeri Bali, focusing on the 2023 and 2024 batches. The primary aim is to understand the intrinsic and extrinsic factors shaping students' entrepreneurial intentions. A mixed-methods approach was employed, combining observation and in-depth interviews to gather qualitative data. The study examines the role of personal motivations, such as self-drive and prior entrepreneurial experiences, alongside external influences like family support and income potential. The analysis revealed that intrinsic factors, particularly self-motivation and early exposure to entrepreneurship, were more influential in fostering entrepreneurial intentions than extrinsic factors. Students with higher intrinsic motivation were more inclined to pursue entrepreneurial ventures independently. Challenges identified included a lack of practical experience and limited access to capital, which hindered students' entrepreneurial efforts. Although support from family and the local community played a role, the impact was less significant compared to personal desires and the satisfaction derived from running a business. In conclusion, intrinsic motivations are the primary drivers of entrepreneurial intention among the students, with external factors serving as secondary influences. To support students' entrepreneurial aspirations, addressing challenges like practical experience and access to resources is crucial.